2010
DOI: 10.1016/j.jmb.2009.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between Closely Related Cellular Metabolites by the SAM-I Riboswitch

Abstract: The SAM-I riboswitch is a cis-acting element of genetic control found in bacterial mRNAs that specifically binds S-adenosylmethionine (SAM). We previously determined the 2.9-Å X-ray crystal structure of the effector-binding domain of this RNA element, revealing details of RNA-ligand recognition. To improve this structure, variations were made to the RNA sequence to alter lattice contacts, resulting in a 0.5-Å improvement in crystallographic resolution and allowing for a more accurate refinement of the crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 49 publications
7
88
2
Order By: Relevance
“…2A), which is conserved in SAM-I and SAM-I/IV but is a G-C pair in SAM-IV. Mutation of this A-U pair to G-C in the TteSAM-I and Bacillus subtilis yitJ SAM-I aptamer domains results in a moderate loss in affinity (10,20). Despite the identical SAM-binding cores (within the coordinate error of the known structures), the crystal structure of env87 (ΔU92) reveals a completely novel peripheral architecture surrounding the core in the SAM-I/IV aptamer.…”
Section: Rna Crystallization and Structure Determinationmentioning
confidence: 95%
“…2A), which is conserved in SAM-I and SAM-I/IV but is a G-C pair in SAM-IV. Mutation of this A-U pair to G-C in the TteSAM-I and Bacillus subtilis yitJ SAM-I aptamer domains results in a moderate loss in affinity (10,20). Despite the identical SAM-binding cores (within the coordinate error of the known structures), the crystal structure of env87 (ΔU92) reveals a completely novel peripheral architecture surrounding the core in the SAM-I/IV aptamer.…”
Section: Rna Crystallization and Structure Determinationmentioning
confidence: 95%
“…2B). 27,38,49,50 The binding site is constituted by the minor grooves of helices P1 and P3, in which the SAM adenine moiety interacts with a bulge located in the P3 stem. The methionine group of the ligand is involved in interactions with the J1/2 region.…”
Section: Folding Of the Sam-i Riboswitchmentioning
confidence: 99%
“…A study has reported the existence of SAH-sensing riboswitches, 37 indicating that SAM/SAH riboswitches exploit chemical differences between closelyrelated metabolites to prevent cellular misregulation, which is consistent with recently obtained crystal structures. 38 SAM riboswitches have also been found in tandem arrangement with a coenzyme B 12 riboswitch, where both riboswitches function as a two-input Boolean NOR logic gate. 39 Figure 1.…”
Section: S-adenosylmethionine (Sam) Riboswitchesmentioning
confidence: 99%
“…The crystal structures of the SAM-I riboswitch in Thermoanearobacter tencongensis upstream of the metF-H2 gene and in B. subtilis upstream of the yitJ gene revealed that SAM binds to a pocket formed by four coaxially stacked helices (P1, P2, P3, P4) joined by junctions J1/2, J2/3, and J3/4 ( Fig. 1; Montange and Batey 2006;Lu et al 2010;Montange et al 2010). Mutational analysis and biophysical studies show that a kink-turn-mediated pseudoknot formation assists the global folding of the riboswitch cooperatively with Mg 2+ present (Winkler et al 2001;McDaniel et al 2005;Heppell and Lafontaine 2008;Lu et al 2010).…”
Section: Introductionmentioning
confidence: 99%